2022
DOI: 10.1097/j.pain.0000000000002669
|View full text |Cite
|
Sign up to set email alerts
|

Maddalena Opioid Switching Score in patients with cancer pain

Abstract: An integrated score, taking into account pain and adverse effect intensity, provides simple data easy to compare in research studies of opioid switching for cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…We observed, as have others [9,10,12,13,18], that the opioid switch group represented a population of patients with difficult pain control. At the baseline, patients in the switch group experienced worse pain (background, breakthrough, and incident pain), more neuropathic pain (a higher S-LANNS score), a greater influence of pain on function (functional items from the BPI), adverse effects (items from ESAS), and psychological distress (one item from ECS-CP).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We observed, as have others [9,10,12,13,18], that the opioid switch group represented a population of patients with difficult pain control. At the baseline, patients in the switch group experienced worse pain (background, breakthrough, and incident pain), more neuropathic pain (a higher S-LANNS score), a greater influence of pain on function (functional items from the BPI), adverse effects (items from ESAS), and psychological distress (one item from ECS-CP).…”
Section: Discussionsupporting
confidence: 82%
“…Studies have reported improvements in similar pain score outcomes post-switch. For example, recently, Mercadante et al [10] found a similar post-switch ESAS pain score reduction to 3.48 at a median of 6 days. Other studies using other scoring systems on a 0-10 scale (e.g., visual assessment scale, independent numerical rating scale) have also found pain outcomes of 3 or less at 3-14 days post-switch [3,13].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Of interest, we reported data of complete successful OS in patients who were then discharged home, avoiding confounding terms such as partial success (21). In fact, patients who were reported to be successfully switched also reported a positive patient's global impression (11).…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-ve patients who were admitted to an Acute Supportive/Palliative Care Unit (ASPCU) and had a successful OS were selected from a sample of a concomitant study assessing a tool for monitoring the outcomes of OS (11).from January 1, 2020, until June 30th 2021 (11).…”
Section: Methodsmentioning
confidence: 99%